The microbiology of ethmoid and maxillary sinuses in patients with chronic sinusitis - Aral, M; Keles, E; Kaygusuz, I (W B Saunders Co-Elsevier Inc, 2003)
Purpose: To investigate aerob-anearob microorganisms growth in maxillary and ethmoid sinuses by evaluating aspiration materials from patients with chronic sinusitis. Patients and Methods: The study was performed prospectively, and there were 31 patients (23 men, 8 women; mean age, 31.4 +/- 14.15, between 18-65 years) who had endoscopic sinus surgery because of chronic sinusitis. During the operation, when the maxillary sinus ostium and ethmoid sinus were opened, readily aspirated materials from sinuses were evaluated regarding aerob and anaerob bacteria. Nose and throat swap samples were collected preoperatively to determine the upper respiratory tract flora and also to understand the relationship between the flora and the microorganisms aspirated from sinuses. Results: Total aerob bacteria count, which was isolated from preoperative nasal swab cultures, was 36, and aerob-anaerob bacteria count that included cultures taken from maxillary and ethmoid sinuses during the functional endoscopic sinus surgery was 42. For each 2 samples, the most common isolated aerob bacteria were coagulase (-) staphylococci. Microorganisms were isolated in 87.0% of 27 patients, in which cultures taken from maxillary and ethmoid sinuses during the functional endoscopic sinus surgery were included. It is determined that the isolated aerob bacteria rate was 90.4%, and the isolated anaerob bacteria rate was 14.2%. All of the 6 samples in which anaerob bacteria isolated were all maxillary sinus aspiration materials. Microorganisms that isolated from the nose and the sinuses were similar with the rate of 25.8%, and microorganisms that isolated from the throat cultures and sinuses were similar with the rate of 22.5%. Conclusions: This study reveals the aerob and anaerob microbiology of the maxillary and ethmoid sinuses so the treatment of chronic sinusitis will be easier.
Keywords: Bacteriology; Management; Rhinosinusitis; Nasal